Variability in morphological traits as a reproductive strategy in a lizard model - Chiaraviglio, Margarita (2013)
FIL: Chiaraviglio, Margarita. Universidad Nacional de Córdoba. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Diversidad y Ecología Animal; Argentina.